Modeling and Simulation Analysis of DC/DC High Frequency Isolated Converter Based on Average State Space Method - 王小方 (机车电传动)
For obtaining steady state, transient and dynamic characteristics, average state space method was proposed to the modeling and simulation analysis in DC/DC high frequency converter of 70 kW passive buffer type soft-switching isolated converter. Firstly, the converter equivalent circuit was established on the condition of considering the transformer leakage inductance, output filter inductor and capacitor equivalent circuit resistance. Secondly, analyzed the key voltage, current ideal waves in a cycle, and drew the equivalent circuits under different states. Thirdly, in order to obtain the small-signal transfer function in continuous work mode, the average and linearization method was to deal with the state variable equations. Last, double-loop control system was set up in accordance with the mathematical model, and MATLAB was used to verify the rationality of that model.